2020
DOI: 10.1080/0144235x.2020.1792104
|View full text |Cite
|
Sign up to set email alerts
|

Criegee intermediates: production, detection and reactivity

Abstract: In the context of tropospheric chemistry, Criegee intermediates denote carbonyl oxides with biradical / zwitterionic character (R1R2COO) that form during the ozonolysis of alkenes. First discovered almost 70 years ago, stabilized versions of Criegee intermediates formed via collisional removal of excess energy have interesting kinetic and mechanistic properties. The direct production and detection of these intermediates were not reported in the literature until 2008. However, recent advances in their generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 172 publications
(309 reference statements)
0
103
0
Order By: Relevance
“…The former process involves the reaction RO 2 + HO 2 → ROOH + O 2 6 and intramolecular autoxidation of RO 2 leading to the formation of HOM, 7 that contain multiple -OOH groups. The latter process involves reactive carbonyl oxide zwitterions/biradicals, known as Criegee intermediates (CIs), 8 generated by ozonolysis of unsaturated VOCs possessing C=C bond(s) such as biogenic terpenes. CIs can rapidly react with OH-containing species such as water, alcohols and carboxylic acids to form ROOHs in the gas-phase or liquid-phase and at the air-liquid interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former process involves the reaction RO 2 + HO 2 → ROOH + O 2 6 and intramolecular autoxidation of RO 2 leading to the formation of HOM, 7 that contain multiple -OOH groups. The latter process involves reactive carbonyl oxide zwitterions/biradicals, known as Criegee intermediates (CIs), 8 generated by ozonolysis of unsaturated VOCs possessing C=C bond(s) such as biogenic terpenes. CIs can rapidly react with OH-containing species such as water, alcohols and carboxylic acids to form ROOHs in the gas-phase or liquid-phase and at the air-liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…CIs can rapidly react with OH-containing species such as water, alcohols and carboxylic acids to form ROOHs in the gas-phase or liquid-phase and at the air-liquid interface. [8][9][10] The reactions of CIs with ammonia, ammine, HCl, H 2 S also produce ROOHs. 8 Among the reaction partners of CIs, water (H 2 O) n>1 is expected to be the most important reactant because of its predominant abundance in both the gas-phase and the condensed phases.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The simplest Criegee intermediate, formaldehyde oxide (CH2OO) reacts mainly with H2O dimer in the troposphere, 9,10 but larger biogenic Criegee intermediates can react with other trace tropospheric species like NO2, SO2, carboxylic acids, HNO3 and HCl. 11,12 Atmospheric simulation chamber and flow reactor measurements by Zhao et al using mass spectrometric detection have shown that Criegee intermediates from the ozonolysis of trans-3hexene undergo oligomerization reactions with RO2 to produce adducts with several Criegee intermediate chain units. 13 These oligomers were found to have high molecular weights and contribute to particle growth and new particle formation in their experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed QCLs have been used to measure the production of CO in the combustion of n-heptane (Nasir and Farooq, 2019), and have been used to determine the IR absorption spectrum and cross-sections of the Criegee intermediate CH2OO (Chang et al, 2017;Chang et al, 2018b;Luo et al, 2018a). CH2OO is a reactive species produced in the atmosphere during the ozonolysis of unsaturated volatile organic compounds (VOCs) that has been of recent interest as a result of developments in photolytic sources (Welz et al, 2012) for detailed laboratory studies which have revealed a more significant role in atmospheric chemistry than previously expected (Chhantyal-Pun et al, 2020;Percival et al, 2013). Quasi-continuous QCLs, pulsed QCLs in which the pulse period is relatively long compared to the lifetime of the species under investigation, have also been used to investigate the spectra and kinetics of CH2OO (Chang et al, 2018a), and cw QCLs have been used to investigate the kinetics of CH2OO (Luo et al, 2018b;Luo et al, 2019;Li et al, 2019;Li et al, 2020) and other larger Criegee intermediates (Luo et al, 2018b), as well as the spectroscopy and kinetics of the atmospherically important peroxy radicals HO2 (Miyano and Tonokura, 2011;Sakamoto and Tonokura, 2012) and CH3O2 (Chattopadhyay et al, 2018).…”
Section: Introductionmentioning
confidence: 99%